Quality and storage characteristics of yogurt containing Lacobacillus sakei ALI033 and cinnamon ethanol extract. Issue 1 (December 2016) - Choi, Yu; Jin, Hee; Yang, Hee; Lee, Sang; Huh, Chang
Abstract Background This study was conducted to examine the quality and storage characteristics of yogurt containing antifungal-active lactic acid bacteria (ALH, Lacobacillus sakei ALI033) isolated from kimchi and cinnamon ethanol extract. The starter was used for culture inoculation (1.0 % commercial starter culture YF-L812 and ALH). Results The antifungal activity of cinnamon extracts was observed in treatments with either cinnamon ethanol extracts or cinnamon methanol extracts. Changes in fermented milk made with ALH and cinnamon extract during fermentation at 40 °C were as follows. The pH was 4.6 after only 6 h of fermentation. Titratable acidity values were maintained at 0.8 % in all treatment groups. Viable cell counts were maintained at 4 × 109 CFU/mL in all groups except for 1.00 % cinnamon treatment. Sensory evaluations of fermented milk sample made with ALH and 0.05 % cinnamon ethanol extract were the highest. Changes in fermented milk made with ALH and cinnamon ethanol extract during storage at 4 °C for 28 days were as follows. In fermented milk containing ALH and cinnamon ethanol extracts, the changes in pH and titratable acidity were moderate and smaller compared with those of the control. Viable cell counts were maintained within a proper range of 108 CFU/mL. Conclusions The results of this study suggest that the overgrowth of fermentation strains or post acidification during storage can be effectively delayed, thereby maintaining the storage quality of yogurt products in a stable way, using cinnamon ethanol extract, which exhibits excellent antifungal and antibacterial activity, in combination with lactic acid bacteria isolated from kimchi.